Role of Secondary School English Language Teachers in Communicative Language Teaching (CLT) in Tanzania: Visual Methodological Study - Omari, Jafari Abdala (Papers in Education and Development, 2020)
This study intended to explore the role of teachers in communicative language teaching (CLT) classroom in secondary schools in Tanzania. The study involved 71 learners from three secondary schools in Tanga city in Tanzania. It used visual methodologies design and photovoice as a method for collecting data. Learners were asked "Draw a picture or take a picture which represents the role of your English teacher" and Why did you portray your teacher as such? The findings show that the roles of teachers fall within three categories: Transmission, affective and authoritarian. The study recommends for equipping teachers with skills on how to teach English using CLT through various training, seminars and workshops. Keywords: communicative competence, language teaching, secondary school, visual methodology